The Mental Preparation of the Professional Player as One of the Basic Requirements for the Success of Professionalism in Algerian Football "A field study on some of the first and second professional league coaches - charati, rachid (sports creativity, 2025)
The current study aims to attempt to highlight the importance of the mental aspect of the professional football player, and also aimed to identify the importance of mental preparation for the professional football player. It tries to reveal the important and effective role played by the sports psychologist in the life of a professional football player. To verify the study hypotheses we adopted The Descriptive Analytical Approach, and to collect data from the study sample we have used The Questionnaire, which was applied to a sample of (18) coaches who were randomly selected. After obtaining the quantitative data, it was statistically analyzed, Where The researcher has used The Percentages and the Chi-Square Test. After statistically processing the data we reached the following results: The mental preparation of the professional player is one of the basic requirements for the success of professionalism in Algerian footbal